2013
DOI: 10.1002/ijc.28557
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes expressed by immune cells of the colon that are regulated by colorectal cancer‐associated variants

Abstract: A locus on human chromosome 11q23 tagged by marker rs3802842 was associated with colorectal cancer (CRC) in a genome-wide association study; this finding has been replicated in case–control studies worldwide. In order to identify biologic factors at this locus that are related to the etiopathology of CRC, we used microarray-based target selection methods, coupled to next-generation sequencing, to study 103 kb at the 11q23 locus. We genotyped 369 putative variants from 1,030 patients with CRC (cases) and 1,061 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 47 publications
9
55
0
1
Order By: Relevance
“…Fig 2 shows examples of putative shared regulatory sites at the COLCA1 and COLCA2 locus on chromosome 11. Of 4 eQTL variants independently associated with these genes, two are shared by both, consistent with previous studies demonstrating co-regulation between these genes [14]. …”
Section: Resultssupporting
confidence: 89%
“…Fig 2 shows examples of putative shared regulatory sites at the COLCA1 and COLCA2 locus on chromosome 11. Of 4 eQTL variants independently associated with these genes, two are shared by both, consistent with previous studies demonstrating co-regulation between these genes [14]. …”
Section: Resultssupporting
confidence: 89%
“…This cis -eQTL has also been previously reported by several groups for normal colon tissue [1720] and normal rectal tissue [19]. In addition, immunohistochemical evaluation of protein expression profiles were recently reported for COLCA 1 and COLCA2 in normal colon tissue [18]. COLCA1 protein was detected in the lamina propria, extracellularly between epithelial cells, and in immune cells (eosinophils, mast cells, neutrophils, macrophages, and dendritic cells).…”
Section: Discussionsupporting
confidence: 79%
“…21 Previous studies have indicated that COLCA1 plays a role in inflammation and cancer. 22 Moreover, COLCA1 has been implicated as a susceptibility locus for colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%